Odpowiedzi

2009-12-16T23:36:30+01:00
A)25x²+60x+36+37=16x²+48x+36+9x²+30x+25
-18x=-12
x=2/3
b)-17+9x²+6x+1=4x+3+9x²-2x-3
4x=16
x=4
c)36x²-36x+9+29x²+219=16x²-24x+9+49x²-42x+9
30x=-210
x=-7
Najlepsza Odpowiedź!
2009-12-16T23:38:06+01:00
Rozwiąż równania
a) (5x+6)²+37=(4x+6)²+(3x+5)²
25x²+60x+36+37=16x²+48x+36+9x²+30x+25
25x²+60x-16x²-48x-9x²-30x=25+36-36-37
-18x=-12
x=12/18
x=2/3


b) -17+(3x+1)²=(4x+3)+9x²-(2x+3)
-17+9x²+6x+1=4x+3+9x²-2x-3
6x-4x+2x=-3+3-1+17
4x=16
x=4



c) (6x-3)²+29x²+219=(4x-3)²+(7x-3)²
36x²-36x+9+29x²+219=16x²-24x+9+49x²-42x+9
36x²+29x²-16x²-49x²-36x+24x+42x=9+9-219-9
30x=-210
x=-7